Dispositivo fotobiomodulador para o tratamento de traumas mamilares - Suellen Fonseca Santos (2013)
Phototherapy with LED stands as a biostimulator method for promoting accelerated wound healing and pain control. Recently, the pursuit of strategies that would be able to optimize the healing of a specific type of lesion motivated the development of a photobiomodulation dispositive which uses light emitting diodes (LED) with a wavelength in the near infrared spectral range, specific for the treatment of nipple trauma. These lesions, mainly due to pain and discomfort generated for women during the act of breastfeeding may promote early weaning, bringing losses for both the child and to the mother. The aim of this study was to determine the effectiveness of a dispositive photobiomodulation consisting of LEDs with a wavelength in the near infrared spectral range in the treatment of nipple trauma. This is a longitudinal study of the clinical trial placebo-controlled, randomized, double-blind trial in Sofia Feldman Maternity. Seventeen participants with 33 nipple wounds (cracks, fissures and abrasions) were divided into two groups: experimental and control. The experimental group was submitted to standard care (guidance on correct breastfeeding technique and nipple care) and applications of the photobiomodulation dispositive, while the control group received standard treatment and applications of the placebo dispositive. Participants were treated once a day during the period of hospitalization and were subjected to 1, 2 or 3 sessions. The following parameters were used: wavelength of 860 nm, pulsatile emission mode, frequency of 100 Hz, fluency rate of 50 mWcm-2 and fluency of 4 Jcm-2 for 79 seconds. The area of the nipple injury was evaluated, measured by an image analysis software, along with pain intensity, measured by the Visual Numeric Scale. In addition, subjects were monitored for 4 weeks. The analysis showed statistically significant reduction of the area of the nipple trauma in the experimental group compared with the control (p = 0.011). There was a decrease in pain intensity in both groups with increasing sessions, but was statistically significant only in the experimental group (p = 0.004). Furthermore, the results of the follow up showed that the experimental group had, over the weeks, accelerated healing (p = 0.002) and reduction in pain (p = 0.000) when compared to the control group. The results of this study indicate that the device constituted of LEDs photobiomodulator was an effective tool in the treatment of nipple trauma.